The Landscape of Alternative Splicing Regulating Potassium Use Efficiency in Nicotiana tabacum - He, Bing; Meng, Lin; Tang, Lina; Qi, Weicong; Hu, Fengqin; Lv, Yuanda; Song, Wenjing (Frontiers in Plant Science, 2021)
Alternative splicing (AS) occurs extensively in eukaryotes as an essential mechanism for regulating transcriptome complexity and diversity, but the AS landscape regulating potassium use efficiency in plants is unclear. In this study, we performed high-throughput transcriptome sequencing of roots and shoots from allopolyploid Nicotiana tabacum under potassium deficiency. Preliminary physiological analysis showed that root system architecture was dramatically changed due to potassium deficiency and that IAA content was significantly reduced in root and shoot. By alternative splicing analysis, a total of 54,457 AS events from 28,179 genes exhibited AS, with the major AS type being exon skipping, and 1,510 and 1,732 differentially AS (DAS) events were identified in shoots and roots under low K+ stress. Nevertheless, only 120 DAS events occurred in both shoots and roots, implying that most DAS events were tissue-specific. Compared with differentially expressed genes (DEG), only a few genes, including 60 in shoot and 78 in the root, were co-regulated by both expression abundance and AS, which indicated that AS might play a unique regulatory role in response to low potassium. Gene ontology analysis of DAS genes further revealed specific biological processes and molecular functions such as “mRNA processing” (GO:0006397), “DNA repair” (GO:0006281), and “lipid modification” (GO:0030258). Besides, 175 transcription factors (TF) were identified, including 142 DE TFs and 45 DAS TFs. Five ARF transcription factors, for instance, were significant DAS in root and eight ARF transcription factors were DE in shoots, which indicated that the primary transcription regulation pattern of auxin response was expression abundance change in shoot and AS modulation in the root. Our study shows that AS variation occurs extensively and has a particular regulatory mechanism under potassium deficiency in tobacco.